Between Dao（道） and Fa（法）: Light and Heavy Theory（轻重论） in Guanzi Thought structure and the essence of Huang-Lao philosophy（黄老之学） (Journal of humanities and social sciences exploratio, 2025)
Guanzi an important classic compiled under the name of Guan Zhong during the Warring States period, epitomizes the economic philosophy of "Theory of Light and Heavy," which encapsulates the wisdom of macroeconomic regulation and market governance from the pre-Qin era.Based on the text of Guanzi and related research, this article systematically examines the three core elements of "Theory of Light and Heavy": prioritizing the people, regulating prices, and promoting commerce and trade. It reveals the governance logic behind achieving "wealthy country and peaceful people" through attracting the populace, reducing taxes, and intervening in the market.Furthermore, this article delves into the ideological origins of "Theory of Light and Heavy," pointing out the underlying Huang-Lao Taoist undertones within its ostensibly Legalist governance, such as the concepts of "Tao gives rise to law" and "benefiting the people." It further elucidates the practical development of Huang-Lao thought in "Guanzi," transforming Taoist philosophies into actionable economic policies through strategies like "price stabilization" and "fair reward." The study suggests that "Guanzi's" Theory of Light and Heavy not only laid the economic foundation for the prosperity of the State of Qi but also provided vital resources for the formation of ancient economic thought systems, offering insights for contemporary market economy governance.
Keywords: Guanzi; "On Light and Heavy"; economic thought; Huang-Lao Taoism; macroeconomic regulation and control; people-oriented